Tail Parameters of Stable Distributions Using One Million Observations of Real Estate Returns from Five Continents - Michael Stein; Daniel Piazolo; Stoyan V. Stoyanov (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This study focuses on global real estate return distributions. For our analysis, we employ the class of stable distributions that has become prominent in the real estate literature. We add to the literature by undertaking a global-scale analysis for the first time. By using data since the early 1990s, we show that there is considerable variation in the tail weights of return distributions, both between countries as well as among sectors within the countries. It is important to note that the tail parameters vary over time as well. Our results strengthen the recently discovered notion about non-constant tail parameters in stable distributions, which contradicts earlier findings about constant tail parameters. Additionally, we argue that merely changes over time were to be discovered, rather than pure methodological facts driving the variation, which is in contrast to the initial assumption associated with constant tail parameters. Our results provide an extensive overview of the tailedness of global real estate markets and offer a comprehensive insight into differing market distributions. – – Diese Studie widmet sich den Verteilungen von Immobilienrenditen. Wir verwenden die Klasse der Pareto-stabilen Verteilungen welche sich im Bereich der Analyse von Immobilienrenditen etabliert haben. Wir tragen zur Forschung in diesem Bereich bei, indem wir die erste umfassende globale Analyse liefern. Mit Daten beginnend in den frühen 1990er Jahren zeigen wir dass es deutliche Abweichungen in den Enden der Verteilungen gibt, sowohl zwischen Sektoren, als auch zwischen Ländern. Vor allem aber zeigt sich dass sich die Schwere der Tails im Zeitablauf ändert. Dies bestätigt neuere Ergebnisse für einige Teilmärkte und ist ein Gegensatz zu vormals angenommenen konstanten Parametern für die Stärke von starken Abweichungen.
Keywords: G01; G10; G12; 330; real estate return distributions; stable distributions; tail dependence